Model Sistem Informasi Pendampingan UMKM Berbasis Web - Antonius Wahyu Sudrajat (JuSiTik : Jurnal Sistem dan Teknologi Informasi Komunikasi, 2020)
Efforts to develop MSMEs so that they can compete in global competition are the government's obligation. One form of development that can be done is assisting MSMEs, but mentoring is not only done for MSMEs that already exist or are running but must start from prospective entrepreneurs making business ideas done. The purpose of the Floating model of web-based business advisory information systems is to provide the right candidate for entrepreneurial assistance by mentors who have proven experience and knowledge. To realize this methodology is needed as a framework of reference in implementing development. The steps taken are planning, system analysis, system design and documentation. The Business Assistance Information System Model can bridge potential entrepreneurs and their counterparts to further discuss related ideas or business ideas owned by prospective entrepreneurs so that they can be implemented in real businesses according to the right rules and knowledge without being limited by space and time, namely by utilizing information technology.